How to build a rein tension meter - Eisersiö, Marie (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2013)
A large part of the interactions between horse and rider during horseback riding takes place through the reins and the bit and devices for measuring the tension on the reins, rein tension meters, has fairly recently been developed. To safeguard the welfare of the ridden horse riders need to be aware of the rein tension they apply and actively work to decrease it. Furthermore, there is a need to develop the study of rein tension through new techniques and refined analysis procedures. A good-quality rein tension meter should be small in size, sensitive, durable and as accurate for light rein tension as for strong forces. Rein tension meters used in research on horse and rider interaction commonly depend on strain gauge technique for generating rein tension data. Strain gauges are electrical resistances and when subjected to tension or compression the resistance change. By connecting the strain gauges in a Wheatstone bridge circuit the sensitivity of the measure is increased and the circuit is compensated for temperature changes. The aim of this project was to create a durable rein tension meter at a low cost that would be as accurate for high loads as for small changes of tension. The rein tension meter was made from bent stainless spring steel, strain gauges, a custom made amplifier and electric cable. Three different sizes of steel, 140*40*1 mm (large), 110*35*1 mm (medium) and 90*30*1.5 mm (small) and two different types of strain gauges, pairs of parallel strain gauges and pairs of perpendicular strain gauges, were tested. Power and logging of data was supplied through an Inertial Measurement Unit. The rein tension meters were calibrated by lifting known weights and were tested at local riding schools as well as with privately owned horses. The maximum force the steel could withstand was calculated and the stability of the output voltage to the same weight was tested. A polynomial regression calculation was used to convert the voltage output received from the ridden tests into rein tension in kilograms.